Evaluation of recycled oil refining techniques for biodiesel production - Silva, Carmem Cícera Maria da; Fonseca, Gustavo Graciano (Brazilian Journal of Production Engineering, 2021)
Recycled oil is a raw material option for the production of biodiesel. It has environmental and economic advantages, but there are disadvantages in the production of biodiesel, such as the presence of residues from the oxidation reactions that occur during frying. The recycled oil arrives at the biodiesel producer with these impurities and acidity above the desired standard. Therefore, it needs additional treatments, such as chemical neutralization. This process is widely used by oilseed industries and biodiesel producers, but it has disadvantages for treating oils with high acidity. Environmentally correct and innovative treatments for oils have been the subject of recent research aiming at lower impacts on the raw material and the formation of residues (or formation of higher value-added co-products). This study aimed to present physical refining as an substitute process for treating recycled oils in the biodiesel production process, performing a comparative evaluation as chemical refining, through determinations of yield and physicochemical parameters. The results obtained showed that the physical refining treatment resulted in a 32.59% reduction in the acidity index, while the chemical refining treatment was 92.11%, both in relation to the acidity index of the initial oil. On the other hand, the comparison of yield between the two techniques showed that the physicist showed an increase of 51.09% in relation to the chemical, without causing the formation of sludge and residues. Through physical refining there was the formation of free fatty acids that can have several industrial applications in fine chemistry as opposed to chemical.